Genetic divergence among sugary and nonsugary cassava accession - Vieira, Eduardo Alano; Fialho, Josefino de Freitas; Faleiro, Fábio Gelape; Bellon, Graciele; Fonseca, Kenia Graciele da; Carvalho, Luiz Joaquim Castelo Branco; Silva, Marilia Santos; Paula-Moraes, Silvana Vieira de; Filho, Mário Ozeas Sampaio dos Santos; Silva, Karina Nascimento da (Pesquisa Agropecuaria Brasileira, 2009)
The objective of this work was to estimate the genetic divergence among sugary and nonsugary cassava accessions, through molecular markers, and quantitative and qualitative characters, as well as to determine the correlation among these estimates. Four sugary cassava accessions and four nonsugary ones were used, including two landraces and two nonsugary improved varieties. The accessions were evaluated in field conditions and in laboratories, with RAPD markers, in 12 quantitative and 33 qualitative characters. Matrixes of genetic dissimilarity/distance among accessions were estimated, based on qualitative and quantitative characters, molecular markers, and on the correlation significance among matrixes. High genetic divergence among the evaluated accessions was observed, the sugary accessions were differentiated from the landraces and improved nonsugary varieties. The distances estimated through molecular markers and qualitative characters showed the high association among each other and moderate association with the distance estimated through quantitative characters.